The Issue of Gender in Educational Inequalities in Post New Labour England. An Outline of the Problem - Rutkowska-Lis, Olga (Wydawnictwo Naukowe UAM, 2015)
The paper presents some of the problems referring to the issue of gender gap when considering educational inequality with the focus on England. Interestingly, the problem of educational inequality or inequality as such has been the focus of researchers’ attention for quite a while. However, there seems to be a lack of solid data allowing to draw better conclusions referring to the interconnections of gender and inequalities. There seems to be a general agreement that the problem of gender gap in educational environments is later negatively reflected on professional life and career. Yet, there is little research proving this belief right. The reasons behind the problem of gender and gender gap may be rooted in the complexity of the matter. It is rather difficult to precisely define and name everything that may and should be involved in a gender related research. It also seems to call for more psychologically oriented terms, which forms yet greater challenge for any sociologist. Calling upon the data present, researchers tend to interpret the same sets differently due to employing varying theories, which further muddles the issue of gender, gender gap and its possible relation to educational inequalities. The article is aimed at showing some of the aforementioned problems within the context of educational inequalities in England. It is merely an attempt calling professional circles if not policy writers, to take a step back and rethink the issue of gender inequalities within the context of education.
Keywords: gender; gender gap; educational inequalities; attainment